2016
DOI: 10.1111/codi.13117
|View full text |Cite
|
Sign up to set email alerts
|

Progress in the management of retrorectal tumours

Abstract: This study demonstrated that MRI should be the investigation of choice for retrorectal lesions. Biopsy of solid lesions is safe and useful for guiding neoadjuvant and surgical therapy. Cystic lesions without suspicious radiological features can be followed by serial imaging without resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 21 publications
(35 reference statements)
0
25
0
Order By: Relevance
“…Although recent studies such as that by Hopper et al . have demonstrated that cystic lesions may be managed non‐operatively, the present review suggests that provided the patient is fit for surgery benign lesions should be resected. This is because a benign lesion can be complicated by infection and cause compression of the presacral nerves or obstructive symptoms and vague abdominal discomfort.…”
Section: Discussionmentioning
confidence: 77%
“…Although recent studies such as that by Hopper et al . have demonstrated that cystic lesions may be managed non‐operatively, the present review suggests that provided the patient is fit for surgery benign lesions should be resected. This is because a benign lesion can be complicated by infection and cause compression of the presacral nerves or obstructive symptoms and vague abdominal discomfort.…”
Section: Discussionmentioning
confidence: 77%
“…As another result of this study, the specificity of distinguishing between benign or malignant disease by imaging method was 81% and sensitivity was 83% [15]. In another study, it was concluded that it could be helpful in the diagnosis of Ewing's sarcoma, neurofibrosarcoma, or desmoid tumor, which may receive benefits from preoperative biopsy and neoadjuvant therapy [10,16]. More importantly, a careless transrectal needle biopsy of meningocele can cause undesirable consequences such as meningitis, and even subsequent death [17].…”
Section: Discussionmentioning
confidence: 62%
“…The most common imaging modalities are CT and MRI [10,11]. MRI is preferred over CT because it predicts benign or malignant characteristics of the tumor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They demonstrated a 95% sensitivity for differentiating benign from malignant tumors with the MRI. They also performed a biopsy only to the solid lesions, performing surgery only to 27 of the 65 lesions highlighting the importance of the MRI in the management of this lesion [8].…”
Section: Discussionmentioning
confidence: 99%